Potential And Challenges In Creative Economy Development In Depok City: SWOT Analysis And Strategic Recommendations - Imam Budi Hartono; Prijono Tjiptoherijanto; Chotib Chotib; Sri Listianti Wulandari; Fathir Fajar Sidiq (Universitas Sultan Ageng Tirtayasa, 2023)
The creative industry in Depok City shows positive growth, contributing significantly to the city's Gross Domestic Product (GDP). This article explores the potential and challenges of creative economy development in Depok using SWOT analysis. Although the COVID-19 pandemic has had a negative impact on the economy in general, the creative economy in Depok continues to grow and develop as one of the mainstay sectors supporting regional economic growth. The research also noted that the understanding of the community and related agencies regarding the prospects of the creative industry is still minimal. Therefore, there need to be further efforts to maximise the potential of the creative industry in this city. The purpose of this study is to map the strengths, weaknesses, opportunities, and threats of the creative economy potential in Depok City, along with strategic recommendations for its implementation. This research is expected to serve as a guide for the Depok City Government and related stakeholders in planning and implementing interventions that support the development of the creative economy in Depok City, especially post-pandemic.